Relationship of Freshwater Fish Recruitment With Distinct Reproductive Strategies and Flood Attributes: A Long-Term View in the Upper Paraná River Floodplain - Oliveira, Anielly Galego de; Lopes, Taise Miranda; Angulo-Valencia, Mirtha Amanda; Dias, Rosa Maria; Suzuki, Harumi Irene; Costa, Isadora Cristina Bianchi; Agostinho, Angelo Antonio (Frontiers in Environmental Science, 2020)
The flood pulse is the main driving force for communities’ structure and functioning in river-floodplain systems. High synchrony exists between the hydrological cycle and reproductive cycle events for several fish species. However, species with different reproductive strategies can respond in different ways to the flood regime. Thus, this study intends to evaluate the relationship between the recruitment of different reproductive guilds of freshwater fish and flood attributes (flood duration, maximum annual water level, and delay of flood) from a time series of 20 years in the Upper Paraná River floodplain, Brazil. The abundance of four guilds was evaluated: (i) long-distance migratory with external fertilization and without parental care (LMEF); (ii) non-migratory or short-distance migratory with external fertilization and without parental care (NEFW); (iii) non-migratory or short-distance migratory with external fertilization and parental care (NEFP); and (iv) non-migratory or short-distance migratory with internal fertilization and without parental care (NIF). Multiple regression analyses were applied between flood attributes and abundance of young-of-the-year or juveniles for each reproductive guild. This study observed a consistent pattern of long-lasting flooding positively influencing the recruitment of all reproductive guilds, while water level intensity and the time of the onset of flooding also influenced some non-migratory strategies. We can conclude that the conservation of fish populations and the maintenance of ecosystem functions and services associated with them need to be considered in the operating protocols of upstream hydroelectric plants, since they are dependent on the flooding controlled by them.